Doğal Dil Çıkarımı Modellerinde Bert Vektörlerinin Başarım Değerlendirmesi - Tekir, Selma; Oğul, İskender Ülgen; Oğul, İskender Ülgen; Tekir, Selma (Institute of Electrical and Electronics Engineers Inc., 2021)
Doğal dil çıkarımı, düşünce ifade eden cümlelerin arasındaki ilişkiyi; karşıtlık, gerekseme veya tarafsızlık olarak sınıflandırmayı hedefler. Sınıflandırma görevini gerçekleştirmek için metinsel kaynaklar, vektör ya da gömme olarak adlandırılan matematiksel gösterimlere dönüştürülür. Bu çalışmada, hem statik (Glove, OntoNotes5) hem de bağlamsal (BERT) kelime gömme yöntemleri kullanılmıştır. Fikirsel cümleler arasındaki mantıksal ilişkilerin sınıflandırılması zordur zira cümleler karmaşık gramer yapılarına sahiptir ve cümlelerin işlenerek mantıksal gösterimlere dönüştürülmesi geleneksel doğal dil işleme çözümleri ile yetersiz kalmaktadır. Bu çalışma, sınıflandırma görevini gerçekleştirmek için ayrıştırılabilir ilgi ve doğal dil çıkarımı için gelişmiş LSTM (ESIM) derin öğrenme modellerini kullanmıştır. En iyi sonuç olan %88 doğruluk değeri SNLI veri kümesi üzerinde ESIM-BERT ile elde edilmiştir.

Natural language inference aims to classify the binary relation between opinionated sentences as a contradiction, entailment, or neutral. To accomplish the task, classifiers transform textual data into numerical representations called vectors or embeddings. In this study, both static (Glove, OntoNotes5) and contextual (BERT) word embedding methods are used. Classifying the logical relationships between opinionated sentences is difficult. These sentences have complex grammatical structures to convert them into logical representations, and traditional natural language processing solutions are insufficient to meet the requirement. This study uses Decomposable Attention and Advanced LSTM for Natural Language Inference (ESIM) deep learning methods to perform this classification. The best accuracy score is achieved with 88% using ESIM - BERT on the SNLI corpus. © 2021 IEEE.
Performance Evaluation of Bert Vectors on Natural Language Inference Models
29th IEEE Conference on Signal Processing and Communications Applications, SIU 2021 -- 9 June 2021 through 11 June 2021
Keywords: BERT; Decomposable Attention; ESIM; Natural Language Inference; SNLI